Hubungan Kesadaran Metakognitif Peserta Didik Dengan Hasil Belajar Biologi - Ai Anisa Asaidah; Romy Faisal Mustofa; Diki Muhamad Chaidir (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
This study aims to determine the correlation of metacognitive awareness with biology learning outcomes of students in class XI IPA MA Negeri 1 Tasikmalaya City which was conducted in May 2021. This research is a correlational study. The population in this study were all students of class XI IPA MA Negeri 1 Tasikmalaya City as many as 4 classes. The sample selection in this study used a purposive sampling technique as many as 67 students of class XI IPA 3 and class XI IPA 4. The data collection techniques used in this study were questionnaires and interviews. The results of data analysis showed that there was a relationship between metacognitive awareness and biology learning outcomes with a correlation coefficient value of 0.531 meaning that it had a moderate correlation, and a significance value of 0.000 <0.05 was obtained. The conclusion of this study is that there is a relationship between metacognitive awareness and learning outcomes of biology class XI IPA MAN 1 Tasikmalaya City.